STUDI DAN SIMULASI VIDEO DEKODER H.261 - Made Oka Sidyantara , I
Abstract : The H.261 standard defines the video coding and decoding methods for digital transmission over ISDN at rates of p x 64 kbps, where p is in range of 1 - 30. The video bit rates will lie between approximately 64 kbps and 1920 kbit/s. The research made and focused only on decoder mechanism that realized by software-based. The decoder H.261, designed to be able to identify compressed video bit stream. Identification is carried out to obtain coding parameter to make decoding process properly. Decoding algorithm based on DCT image decompression and motion compensated interframe prediction. Image data processed in macroblock, where macroblock consist of four 8x8 blocks of luminance sample, one 8x8 block of Cr samples and one 8x8 block of Cb sample. Each macroblock is decoded using one of several possible modes including intra-decoding (where no motion prediction is used), inter-decoding (which uses motion prediction.) Decoder input originated from network by using TCP/IP protocol. To indicate noise influence exists on network, this research also implement noise generation mechanism on transmission system and bit stream detection process in decoder end. Result of the research indicates that data transmission rate influenced to the quality of video sequence significantly. Bit rate controlling with varying quantization step size (rate control) produces a variable video sequence quality. Bit error reduce quality of H.261 video that identified by PSNR deterioration. Some of PSNR reducing values occurred exactly on several frames, due to temporal propagation of error and depend on where error took place in transmitted bit stream .